Seismic performance of staircase under earthquake loading - Norshakila, Abdul Wahab (2016)
Staircase is the part of secondary system of the structures and it is one of the essential parts of a building because of its functional importance. When compared to the modern escalators, staircase serves not only better in emergency conditions (such as fire escapes, natural disaster, and others) but also provides considerable stiffness to the building. Seems many research of earthquake proves that staircase in reinforced concrete (RC) building suffered severe damage during Wenchuan earthquake at China. Besides, nowadays earthquake from others country had been affected by Malaysia. Therefore, modal analysis of staircase by using SAP2000 software are conducted for Malaysia as to study the influence of earthquake load to the stiffness, displacement and acceleration of stair. This paper deals with the seismic performance of staircase and in particular on the acceleration and displacement that could have their critical and weak points in the stair members. The stair increases structural strength and stiffness of a structure but attracting seismic forces it could fail into its short columns or into the slabs due to high shear forces, into inclined beams supporting the steps a cause of high axial forces. The structural solutions and design practice of stairs in seismic load designed structures are investigated to define their behavior under earthquake loading and to understand their performance. Some calculation and explanation of stair are herein presented. In particular, one type of stair is considered: the one with free standing landing in order to analyze the dynamic characteristics of stair under seismic load. The modal analysis emphasizes the different modal behavior considering the stairs. This modal analysis shown 12 shape of mode of staircase that had been put of the seismic load. From the mode shape, staircase shown its own frequencies and natural time period.